Impact of Race and Ethnicity on Outcomes for Children Waitlisted for Pediatric Liver Transplantation - Mogul, Douglas B. (J Pediatr Gastroenterol Nutr, 2018)
OBJECTIVE: African Americans and other minorities are known to face barriers to health care influencing their access to organ transplantation but it is not known whether these barriers exist among pediatric liver transplant waitlist candidates. We sought to determine whether outcomes on the waitlist (i.e., mortality, deceased donor liver transplantation (DDLT), and living-donor liver transplantation (LDLT)) varied by race/ethnicity. METHODS: National registry data were studied to estimate the race/ethnicity-specific risk of waitlist mortality, DDLT and LDLT in children (<18 years) waitlisted between March, 2002 and March, 2015. RESULTS: There was no evidence of racial/ethnic disparities in waitlist mortality. Compared to Caucasians, LDLT varied by race/ethnicity, with only 6.7% African Americans and 10.3% Hispanic children receiving LDLT compared with 12.4% Caucasian, 13.3% Asian, and 9.4% mix/other children. In an adjusted Cox proportional hazards model, African Americans were half as likely as Caucasians to use LDLT (hazard ratio (HR): (0.41)0.55(0.73)) but had similar use of DDLT (HR: (0.98)1.06(1.16)). In a model that considered mortality, DDLT, and LDLT as competing risks, African Americans had significantly reduced incidence of LDLT (subhazard ratio (sHR): (0.41)0.56(0.75)) compared to Caucasians, but increased use of DDLT (sHR: (1.06)1.16(1.26)). CONCLUSION: Compared to Caucasian children, African-American children are less likely to use LDLT but have higher rates of DDLT and similar survival on the waitlist. Additional research is necessary to understand the clinical and socioeconomic factors contributing to lower utilization of LDLT among African-American children awaiting transplantation.